The effect of amaranthus tricolor on hemoglobin levels in adolescent girls: Literature reviewe - Dilma'aarij Agustia; Wiwiek Elsada Nainggolan; Ruth Yohana Girsang; Novitri Adelina Sipayung; Yusmalia Hidayati (Institute of Computer Science (IOCS), 2026)
Iron deficiency anemia remains a major health problem among adolescent girls, often caused by low iron intake and poor absorption. Amaranthus tricolor (red spinach) is a local vegetable known to contain high levels of iron, vitamin C, and antioxidants that support iron absorption. This literature review aimed to analyze the effect of Amaranthus tricolor on hemoglobin levels in adolescent girls. The literature search followed the PRISMA flow using databases such as PubMed, Google Scholar, SpringerLink, and Science Direct for studies published between 2015–2025. Inclusion criteria were full-text articles in Indonesian or English with randomized controlled trial or quasi-experimental designs involving adolescent girls aged 10–18 years. Four studies met the eligibility criteria. Results showed that administration of red spinach extract, tea, or capsule forms significantly increased hemoglobin levels. One study reported, while others demonstrated higher hemoglobin improvements in the intervention group compared to controls receiving Fe tablets (p < 0.05). Overall, red spinach effectively improves hemoglobin levels through its iron, vitamin C, and antioxidant content, indicating its potential as a functional food for anemia prevention among adolescents. Further high-quality studies are recommended to determine optimal dosage, form, and duration of intervention.